Price formation and optimal trading in intraday electricity markets with a major player - Olivier Féron; Peter Tankov; Laura Tinsi (Risks, 2020)
We study price formation in intraday electricity markets in the presence of intermittent renewable generation. We consider the setting where a major producer may interact strategically with a large number of small producers. Using stochastic control theory, we identify the optimal strategies of agents with market impact and exhibit the Nash equilibrium in a closed form in the asymptotic framework of mean field games with a major player.
Keywords: 330; intraday electricity market; renewable energy; mean field games; major player